2014
DOI: 10.1039/c3qo00067b
|View full text |Cite
|
Sign up to set email alerts
|

Fusarisetins: structure–function studies on a novel class of cell migration inhibitors

Abstract: Herein, we report the effects of fusarisetin A on cell morphology focusing in particular on actin and microtubules dynamics. We also report the synthesis and structure-function studies of a designed library of synthetic fusarisetins in cell-based assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Known compounds 3–6 were identified as fusarisetin B (Ahn et al, 2012), fusarisetin A (Jang et al, 2012), equisetin (Singh et al, 1998), and epi -equisetin (Singh et al, 1998), by comparison of their spectroscopic data with the literature. Compound 3 was previously reported as its enantiomer in a patent, but was cited in another article as fusarisetin B, which corresponds with the structure determined herein (Ahn et al, 2012; Caro-Diaz et al, 2014). Although the structure of 4 was revised in 2012, that of 3 was not, and the determination of its absolute configuration was also not discussed.…”
Section: Resultssupporting
confidence: 78%
“…Known compounds 3–6 were identified as fusarisetin B (Ahn et al, 2012), fusarisetin A (Jang et al, 2012), equisetin (Singh et al, 1998), and epi -equisetin (Singh et al, 1998), by comparison of their spectroscopic data with the literature. Compound 3 was previously reported as its enantiomer in a patent, but was cited in another article as fusarisetin B, which corresponds with the structure determined herein (Ahn et al, 2012; Caro-Diaz et al, 2014). Although the structure of 4 was revised in 2012, that of 3 was not, and the determination of its absolute configuration was also not discussed.…”
Section: Resultssupporting
confidence: 78%
“…It was reported that fusarisetin A also has acinar morphogenesis inhibitory activity [63]. Interestingly, fusarisetins A and B are considered as a novel class of potent cancer migration inhibitors with a new mechanism of action [64,65]. The SAR of the fusarisetins revealed that the decalin motif, serine amino acid, and C-18 oxygen are critical to the biological profile of fusarisetins [64].…”
Section: -Decalinoyltetramic Acidsmentioning
confidence: 99%
“…recently suggested that fusarisetin A and equisetin were both biosynthetic derivatives of the polyenoylamino acid 82 . Recently, Theodorakis and co‐workers reported structure–function studies by synthesizing fusarisetin A analogues to interrogate the biological significance [39]. From a structural perspective, the spiroskeleton of rings C and E, bearing a quaternary stereocenter at the angular position of the 5,5,5‐fused tricyclic scaffold, could be made from amide 75 via a Dieckmann‐type cyclization reaction followed by hemiacetalization.…”
Section: Recent Syntheses Of the Exemplified Natural Productsmentioning
confidence: 99%